The Influence of Product Quality, Brand Image, and Promotion on Purchase Decisions (A Study of Consumer Purchases of Coconut Pudding in the Barlingmascakeb Region) - Iqbal Nafis Abiansyah; Irawan Randikaparsa; Tri Septin Muji Rahayu; Alfato Yusnar Kharismasyah (LP2M IAIN Palopo, 2026)
This study aims to examine the influence of product quality, brand image, and promotion on purchase decisions of coconut pudding products, employing cognitive and affective theories as the grand theoretical framework. A quantitative research design was applied, with data collected through purposive sampling involving 267 respondents. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess the relationships among variables. The findings indicate that product quality, brand image, and promotion have a positive and significant effect on purchase decisions. These results highlight the importance of implementing an integrated marketing strategy that emphasizes product quality enhancement, effective brand management, and promotional effectiveness to stimulate consumer purchase decisions.